Nanotechnology approaches towards biodeterioration-resistant wood: A review - Ayyoob Arpanaei; Qiliang Fu; Tripti Singh (Journal of Bioresources and Bioproducts, 2024)
Wood can be a suitable alternative to energy-intensive materials in various applications. Nevertheless, its susceptibility to weathering and decay has significantly hindered the broad adoption of the most commercially significant wood species. While current solutions do tackle certain challenges, they often come with disadvantages like high costs, environmental risks, and/or inefficiencies. Nanotechnology-based methods can be employed to mitigate these weaknesses and create durable, sustainable wood materials. In this review, we delve into cutting-edge advancements in the development of biodeterioration-resistant wood through innovative nanotechnology approaches. These methods usually involve the application of nanomaterials, either possessing biocidal properties or serving as carriers for biocides. We systematically describe these approaches and compare them to conventional wood modification methods. Additionally, this review provides a brief overview of the prevalent biodeteriorating organisms and their mechanisms of action, which notably impact the development and choice of a suitable strategy for wood modification/treatment. Given the requirements of biodeteriorating organisms for growth and wood degradation, it is expected that the new nanotechnology-based approaches to enhance wood durability may provide innovative broad-spectrum biocidal nanosystems. These systems can simultaneously induce alterations in the physicochemical properties of wood, thereby constraining the availability of the growth requirements. These alterations can efficiently inhibit the biodeterioration process by decreasing water absorption, restricting access to the wood components, and reducing void spaces within the wood structure. Finally, this review highlights the new opportunities, challenges, and perspectives of nanotechnology methods for biodeterioration-resistant wood, through which some techno-economic, environmental and safety aspects associated with these methods are addressed.